Form, Funding and Political Purposes of Urban Parks - Alan Tate (Spool, 2018)
This paper examines the political motivations behind the establishment of public urban parks in western Europe and the United States, and addresses issues affecting the funding of those parks.  It does this through a chronological examination of park development, arguing that the physical form and facilities provided in parks reflect the purposes for which they were designated.  As such, the form and purpose of parks therefore reflect, in their various forms and functions, the intentions and values of their funding agencies. The paper examines principal sources of funding for public parks, and documents current challenges in funding urban parks with public money.